Helpless rich data: The effect of financial openness with dimensionality reduction - H. E. Cha; Doo Kyun Wang; Sherryl Berg-Ridenour (Economies, 2025)
The literature on financial openness is rich, yet the selection of a suitable financial index remains a challenge. In this paper, Principal Component Analysis (PCA) and Factor Analysis (FA) are utilized to reduce the dimensionality of five publicly available financial openness indices. The results of the estimation are unexpected: PCA suggests a negative impact of financial openness on economic growth, while FA yields inconsistent results. Importantly, the negative impact of the institutional component on economic growth is statistically significant. These findings highlight the urgent need for proper institutional readiness to fully realize the benefits of financial openness.
Keywords: F43; G15; O47; 330; financial openness; economic development; principal component analysis; factor analysis